2022
DOI: 10.3390/foods11040593
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gum Arabic Coatings Enriched with Lemongrass Essential Oil and Pomegranate Peel Extract on Quality Maintenance of Pomegranate Whole Fruit and Arils

Abstract: The effects of gum arabic coatings combined with lemongrass oil and/or pomegranate peel extract on freshly harvested mature ‘Wonderful’ pomegranate fruit were studied. Fruit were coated with gum arabic (GA) (1.5% w/v) alone or enriched with lemongrass oil (LM) (0.1% v/v) and/or pomegranate peel extract (PP) (1% w/v). Fruit were packed into standard open top ventilated cartons (dimensions: 0.40 m long, 0.30 m wide and 0.12 m high), and stored for 6 weeks at 5 ± 1 °C (90% RH). Evaluations were made every 2 weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 136 publications
2
9
0
Order By: Relevance
“…Through the calculation of hue values that measure the degree of saturation of color and the evaluation by sensory panelists, a marginally improved color was shown in the studied pomegranates following 1-MCP treatment, especially in 'Moyuruanzi', in comparison to the control (Figures 2d and 5). Acidity affects the taste and color of pomegranate arils [27,41], and previous studies have reported that organic acids of fruit are substrates consumed during storage in respiratory processes [39]. Here, a preventation of the decrease in titratable acids was found in all the investigated arils with 1-MCP treatment during low-temperature storage (Figure 3b).…”
Section: Fruit Qualitysupporting
confidence: 62%
See 1 more Smart Citation
“…Through the calculation of hue values that measure the degree of saturation of color and the evaluation by sensory panelists, a marginally improved color was shown in the studied pomegranates following 1-MCP treatment, especially in 'Moyuruanzi', in comparison to the control (Figures 2d and 5). Acidity affects the taste and color of pomegranate arils [27,41], and previous studies have reported that organic acids of fruit are substrates consumed during storage in respiratory processes [39]. Here, a preventation of the decrease in titratable acids was found in all the investigated arils with 1-MCP treatment during low-temperature storage (Figure 3b).…”
Section: Fruit Qualitysupporting
confidence: 62%
“…In this present study, compared to the control, retarded weight loss was recorded in pomegranate fruit of the five varieties with the 1-MCP treatment during the low-temperature storage (Figure 3f). Moreover, when weight loss is excessive, it will result in browning of the peel and arils and hardening of the rind [7,34,39].…”
Section: Weight Lossmentioning
confidence: 99%
“…Rind (10 × 10 mm) were cut, dried, and mounted on aluminum stubs using double-sided carbon tape and sputtercoated with gold. Comparable magnifications of coated and uncoated 'Kinnow' rind were imaged (Kawhena et al, 2022).…”
Section: Scanning Electron Microscopymentioning
confidence: 99%
“…However, postharvest horticulturists are more interested in technologies, which are not only eco‐safe and health friendly but also cost effective (Eshghi, Karimi, Shiri, Karami, & Moradi, 2022; Prasad et al, 2018). Among the latest approaches, the use of novel eco and health friendly edible coatings is gaining popularity as it lowers the dependency on chemical fungicides, which not only affect human health but also contribute to pathogen resistance (Blancas‐Benitez et al, 2022; Kawhena, Opara, & Fawole, 2022). Further, the consignments of mango get rejected if the chemical residue in the fruit exceeds limits (APEDA, 2022), which encourage farmers/growers to use nonchemical eco‐friendly approaches for postharvest management of mango fruits (Prasad & Sharma, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Its postharvest application bears vast potential in tropical fruit industry (Felicia et al, 2022; Salehi, 2020). Recent reports suggest that some HC coatings bear potentially positive effects on external and internal fruit quality, minimize the moisture loss, microbial entry, and gaseous interchange, thereby prolonging the storage period of the treated fruit (Huang et al, 2021; Kawhena et al, 2022). The food industry witnessed the use of HC coatings in processing sector, which is now explored for its potential use as promising edible coatings in fresh fruit industry (Khalil et al, 2022).…”
Section: Introductionmentioning
confidence: 99%